2024
DOI: 10.3390/life14010091
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Kounis Syndrome: Bridging Clinical Knowledge with Forensic Perspectives

Elena Forzese,
Claudia Pitrone,
Vincenzo Cianci
et al.

Abstract: Kounis syndrome (KS) is an acute coronary syndrome triggered by allergic or hypersensitivity reactions. Incidence rates vary, with studies reporting 19.4 per 100.000 among all admissions and 3.4% among allergy patients. This review explores the expanding understanding of KS, encompassing various manifestations, and focusing on both clinical data and forensic findings useful in performing a diagnosis. The pathophysiology of this syndrome involves a complex interplay between allergic reactions and the cardiovasc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…According to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology guidelines, each mutation found after performing genetic tests should be distinguished as pathogenic, likely pathogenic, of uncertain significance (VUS), probably benign or benign [ 67 ]. Because of the continuous increase in the number of variants described in the literature, performing a post-mortem genetic analysis is of fundamental importance to correctly identify the cause of death in all the cases of ARVC without any evident cardiac structural alterations [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology guidelines, each mutation found after performing genetic tests should be distinguished as pathogenic, likely pathogenic, of uncertain significance (VUS), probably benign or benign [ 67 ]. Because of the continuous increase in the number of variants described in the literature, performing a post-mortem genetic analysis is of fundamental importance to correctly identify the cause of death in all the cases of ARVC without any evident cardiac structural alterations [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other analyses have been performed. In particular, both immunohistochemistry and biochemistry have been proved to be very useful [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to support the occurrence of anaphylaxis, several studies have been reported in the literature, proposing an analysis of different immunohistochemical markers for the activated mast cell detection. Among these suggested markers, both the anti-stem cell factor (which detects the mature forms of mast cells) and anti-CD117 (identifying tissue mast cells) are considered to be useful [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations